How to make comic : menurut para master komik dunia / Hikmat Darmawan ; penyunting, Arief Ashshiddiq. - HIKMAT DARMAWAN; Arief Ashshiddiq (Plotpoint Publishing, 2012)
201,[9] hlm. : ilus. ; 24 cm (3 eks.)